Evaluation of Nutritional Status of Chronic Kidney Disease Patients Undergoing Hemodialysis (Med Phoenix, 2020)
Background: Chronic kidney disease caused by deterioration of renal function is a growing problem in the world. In chronic kidney disease, renal function is decreased and waste can build to high level in blood. Malnutrition is common in chronic kidney disease patient who is related to poor food intake because of anorexia, restricted protein intake, nausea and vomiting.Objective: This study aims to assess the nutritional status of chronic kidney patients undergoing hemodialysis by anthropometric measurement and laboratory investigations.Materials and Methods: A cross-sectional study was conducted in Human Organ Transplant Center, Bhaktapur, Nepal over a period of 3 months (December, 2016 to February, 2017). Total of 53 patients (25 male and 28 female) undergoing hemodialysis were included in this study. Anthropometric measurements like body mass index, midupper arm circumference and laboratory investigation like serum albumin was used to evaluate the nutritional status of chronic kidney patients. The data were analyzed using SPSS version 16.0.Results: Mean age of study population was 43.07±16.1 years. Majority of study subjects belong to age group between 17-61 years (64.16%). On the basis of World Health Organization body mass index classification, 24.52% of patients had fallen in malnourished class whereas 64.15% of the patients had normal nutritional status. Similarly, on the basis of mid-upper arm circumference, 52% of the male patients and 75% of the female patients were malnourished. 54.72% of the patient’s calorie intake was below 1200 Kcal. 56.6% of the patients had low serum albumin indicating malnutrition.Conclusion: In conclusion, this study showed that malnutrition is a common problem in our patients with chronic kidney disease undergoing hemodialysis. Inadequate intake of energy and nutrients, low MUAC values, low BMI and low serum albumin concentration increases the degree of malnutrition.